XPO1 inhibition synergizes with PARP1 inhibition in small cell lung cancer by targeting nuclear transport of FOXO3a. (10th April 2021) - Wang, Jingya; Sun, Tao; Meng, Zhaoting; Wang, Liuchun; Li, Mengjie; Chen, Jinliang; Qin, Tingting; Yu, Jiangyong; Zhang, Miao; Bie, Zhixin; Dong, Zhiqiang; Jiang, Xiangli; et al.
Abstract: Patient mortality rates have remained stubbornly high for the past decades in small cell lung cancer (SCLC) because of having no standard targeted therapies with confirmed advantages at present. Poly [ADP-ribose] polymerase (PARP) inhibitors have shown promise in preclinical models but have had unsatisfactory clinical results in SCLC. By RNA-seq and isobaric tags for relative and absolute quantification (ITRAQ), we revealed that PARP1 inhibition led to the relocalization of forkhead box-O3a (FOXO3a) from nuclear to cytoplasm. By performing co-Immunoprecipitation (co-IP) and CRISPR-Cas9-mediated knockout plasmid we showed that FOXO3a was subject to exportin 1 (XPO1)–dependent nuclear export. We demonstrated the effects of the PARP inhibitor BMN673 on apoptosis and DNA damage were markedly enhanced by simultaneous inhibition of XPO1 in vitro. The combination of BMN673 and the XPO1 inhibitor selinexor inhibited primary SCLC cell proliferation in mini-patient-derived xenotransplants (miniPDXs) and markedly inhibited tumor growth without significant toxicity in xenograft models. The efficacy was enhanced for more than 2.5 times, compared to the single agent. Based on these findings, we further designed a novel dual PARP-XPO1 inhibitor and showed its effectiveness in SCLC. In this work, we illustrated that combining a PARP inhibitor with an XPO1 inhibitor is associated with significantly improved efficacy and tolerability. Dual PARP-XPO1 inhibition restored the FOXO3a balance and activity in SCLC. Collectively, targeting PARP1 and XPO1 opens new avenues for therapeutic intervention against SCLC, warranting further investigation in potential clinical trials. Highlights: PARP1 inhibition led to the relocalization of FOXO3a from nuclear to cytoplasm in small cell lung cancer. FOXO3a was subject to XPO1–dependent nuclear export. The effects of the PARP inhibitor are markedly enhanced by simultaneous inhibition of XPO1 in small cell lung cancer. The combination of PARP and XPO1 inhibition emerges as a promising method for clinical small cell lung cancer treatment.